The effects of a marine reserve on galjoen (Dichistius capensis) at Cape Point, South Africa, and implications for the management of the recreational fishery - Elston, Chantel (Department of Biological Sciences, 2014)
Marine protected areas (MPAs) are gaining credibility in the scientific community because of their duality as a conservation and fishery management tool, but sometimes the actual effects of an MPA fall short of the expected outcomes. Case-by-case studies are needed to understand what works and what doesn’t and this understanding can then be applied to decision making and adaptive management. The galjoen (Coracinus capensis), a surf zone teleost endemic to South Africa, is a popular fish for recreational shore anglers and as such the population has declined to dangerously low levels. Marine reserves were established around Cape Point to try and counteract this decline. This study aimed to determine whether these reserves are having a positive effect on galjoen mortality, density and size. A controlled shore angling program has been running on the Cape Peninsula since 1986 in which anglers use a standardised fishing technique. The anglers record the length of their fishing trip as well as the fork length of the fish they catch. Two sites located in near proximity to each other, one in a reserve and one in an exploited area, were chosen from the data set to compare. This avoided the conflicting problem of major habitat differences. General linear models (GLMs) were used to isolate the effect of area on the catch per unit effort (CPUE) as well as fork length, and a negative log-likelihood function was used to estimate the mortality rate and sex ratio for each area. CPUE increased significantly from of 1.02 ± 0.81 galjoen.angler-¹.hour-¹ in the exploited area to 1.48 ± 0.85 galjoen.angler-¹.hour-¹ in the protected area and fork length increased significantly from 300.69 ± 34.71mm in the protected area to 329.31 ± 40.19mm in the exploited area. The GLMs revealed that the parameters ‘area’ and ‘year’ significantly affected the variation in CPUE and fork length, and that area had the greatest explanatory power in both cases suggesting that the reserve had a positive effect on the galjoen density and size. The mortality estimate for the protected site, which was taken as natural mortality, was 0.55 year-¹ and the mortality estimate at the exploited site was 1.0 year-¹. Fishing mortality (F) was estimated as 0.45 year-¹ which was considered to be close to FMSY. Increases in CPUE over time in the exploited area led to the hypothesis that the reserve is re-stocking adjacent exploited areas. A reduction in F over time suggested that effort is reduced in the exploited study area, but it is unknown whether this effort has been displaced to another area adjacent the reserve. Because conventional fishery management tools are difficult or impossible to enforce for the galjoen stock and because the reserves appear to be positively affecting the galjoen within the reserve, it is suggested that the reserves are the optimal and most efficient conservation and fishery management tool for the galjoen stock.